Features of the Structure of Nouns in Arabic and Uzbek Languages - oʻgʻli, Xoʻjamov Zoxidjon Abdurashid (International Journal on Orange Technologies, 2023)
Along with the general linguistic significance of comparative and typological language learning, it is necessary to emphasize its value in the practice of teaching foreign languages, since the typological description of languages provides a means of diagnosing difficulties that students will have to overcome in the process of mastering foreign languages. The comparative method, being a means of studying the current state of languages, aims to establish the typological similarity of different-structured languages, regardless of their origin.